Experience of First Pregnancy at Teenage Age: Scoping Review - Putri, Silvia Rizki Syah; Astuti, Dhesi Ari (Journal of Health Sciences and Medical Development, 2025)
Adolescent pregnancy is a significant global concern and a major contributor to maternal mortality across high-, middle-, and low-income countries. The risk of maternal death is considerably higher among younger adolescents. This study aims to review evidence-based findings on the experiences of first pregnancy in adolescence. A scoping review methodology was employed following Arksey and O'Malley’s framework, using the PEOS model to guide the research questions. A systematic search was conducted in Wiley Online Library, EBSCO, ProQuest, and PubMed, selecting relevant studies based on predefined inclusion and exclusion criteria. Findings indicate that adolescent mothers’ experiences during their first pregnancy are influenced by their level of knowledge and the support received from husbands, families, and healthcare providers. Poor parent-child communication is identified as a key factor contributing to adolescent pregnancy. Additionally, adolescent pregnancy has significant health and educational consequences. Preventive measures include health promotion programs and personalized interventions. This review highlights the experiences, influencing factors, impacts, and prevention strategies related to adolescent pregnancy, providing insights for future research and policy development.